Active filter current compensation for transmission optimisation - Carpenter, Paul Andrew (Department of Electrical Engineering, 2017)
This dissertation is based on the fact that any m-wire electrical system can be modelled as m-equivalent Thevenin voltages and impedances when viewed from any node. The dissertation describes how to calculate the optimal distribution of currents, so a specific amount of power can flow through and reach the network equivalent Thevenin voltages with minimal losses. The optimal current distribution method uses a recently patented method which calculates the optimal currents for each of the wires which are shown to be obtained from the Thevenin parameters and power flow at any instant in time at any node. Once the ideal currents are found, these can be obtained by active and passive devices to inject a specific amount of power (positive and negative) as to compensate existing currents. The focus is particularly on the proof of concept by simulations and physical experiments with work not specifically described in the patent with more emphasis on the optimisation to active compensation. It is explained and shown how this can be implemented using the Malengret and Gaunt method. This method reduces the cost in application where not all the currents need to be processed through a converter (e.g. inverter) but only the difference between the existing and desired optimal currents. A smaller shunt parallel converter can result with ideal current flow without the need for interrupting the currents as described in the present patent. The methodology is explained and demonstrated by simulation.